2012
DOI: 10.1002/cite.201200149
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Cells and Microorganisms in Wave‐Mixed Disposable Bag Bioreactors at Different Scales

Abstract: Disposable bioreactors have gained an increasing importance in recent years in the pharmaceutical production. Wave‐mixed reactors were among the first systems which were applied. In contrast to stirred tank reactors, wave‐mixed bioreactors are characterized by low shear forces while the gas exchange is realized by the large gas‐liquid interface. Oxygen transfer rates obtained are often in a range between 50 and 300 h–1. By applying nutrient‐limiting fed‐batch cultivations, in which the oxygen consumption of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…This approach minimizes Fab leakage and maintains higher overall yield than cultivation with the nutrient supplementation under high aeration conditions. Since maximum Fab expression is achieved at relatively low aeration rates, Fab production at larger scale could be well accomplished in vessels such as disposable wave-mixed bioreactors [41] that have lower aeration rates compared to stirred bioreactors. The enzyme-based fed-batch system should be well suited to larger scale Fab production as it has been demonstrated well scalable up to pilot plant scale [42] and applicable to disposable bag bioreactors [43].…”
Section: Discussionmentioning
confidence: 99%
“…This approach minimizes Fab leakage and maintains higher overall yield than cultivation with the nutrient supplementation under high aeration conditions. Since maximum Fab expression is achieved at relatively low aeration rates, Fab production at larger scale could be well accomplished in vessels such as disposable wave-mixed bioreactors [41] that have lower aeration rates compared to stirred bioreactors. The enzyme-based fed-batch system should be well suited to larger scale Fab production as it has been demonstrated well scalable up to pilot plant scale [42] and applicable to disposable bag bioreactors [43].…”
Section: Discussionmentioning
confidence: 99%
“…Junne et al demonstrated the application of the CELL-tainer for the cultivation of Escherichia coli [11]. In these cultivations, a glucose-limited fed-batch process was successfully employed to prevent oxygen limitation.…”
Section: Cultivation Of Microbial Cells With High Oxygen Demand In Simentioning
confidence: 99%
“…Several promising approaches, such as cultivation in the CELL-tainer system, have been scaled up to near 150 L [11]. Cultivations with heterotrophic marine microorganisms were successful on the 15 L scale [105], therefore cultivations on this larger scale are envisaged.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 99%
“…Even new formats that propose improved mixing and mass transfer, like e.g. the BayShake R (<90 s, worst case conditions 4 W m −3 and no submerse gassing [26] or Biostat Cultibag R (65 to 800 s at 200 L cultivation volume), due to the geometric shape and mode of operation [34] achieve very similar or slower mixing times.…”
Section: Mixing Times In Different Bioreactor Systemsmentioning
confidence: 99%